2004
DOI: 10.1097/00002030-200411050-00012
|View full text |Cite
|
Sign up to set email alerts
|

Nonoxynol-9 100 mg gel

Abstract: N-9 gel 100 mg caused a significant increase in the rate of genital symptoms and epithelial disruptions compared with placebo. The clinical significance of these epithelial disruptions is unknown. Although these findings alone were not sufficient to cancel the planned phase III study, when considered together with the negative results from the COL-1492 effectiveness trial of 52.5 mg N-9 gel, the decision was made to cancel the planned phase III trial of 100 mg N-9 gel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…As expected, N9 was most toxic for EpiVaginal cells, with an average ET-50 value of 4.9 hours. This confirms previous in vitro and in vivo studies [ 7 , 14 , 15 ]. With an ET-50 value of hours, miconazole nitrate showed very low toxicity in our study.…”
Section: Resultssupporting
confidence: 92%
“…As expected, N9 was most toxic for EpiVaginal cells, with an average ET-50 value of 4.9 hours. This confirms previous in vitro and in vivo studies [ 7 , 14 , 15 ]. With an ET-50 value of hours, miconazole nitrate showed very low toxicity in our study.…”
Section: Resultssupporting
confidence: 92%
“…Secondly and more importantly, our findings suggest that aBV might be associated with more severe disruption of the vaginal epithelium than sBV, and hence lead to a greater increase in susceptibility to infections. By analogy, the spermicide nonoxynol-9 (Hillier et al, 2005) is known to cause accelerated cell-shedding (Niruthisard et al, 1991), thinning (Vincent et al, 2011), disruption (Hoffman et al, 2004) and pro-inflammatory changes (Smith-Mccune et al, 2015) on the vaginal epithelium, and was found to increase women's susceptibility to HIV (Wilkinson et al, 2002), as well as susceptibility to HSV-2 (Cone et al, 2006) and HPV (Roberts et al, 2007) in a mouse model. Since aBV is associated with similar physiological effects on the epithelium, we hypothesize it would be associated with an increased risk of infections.…”
Section: Discussionmentioning
confidence: 99%
“…Surfactants nonspecifically disrupt membranes and were the first molecules to enter clinical trials as candidate HIV microbicides. However, these surfactants were found to be toxic to the cervicovaginal mucosa and resulted in an increased rate of HIV infection in phase III clinical trials (54,55). Entry inhibitors prevent HIV from binding to or entering cells and encompass a wide range of molecules, including CCR5 inhibitors (56)(57)(58) and fusion inhibitors (59,60).…”
Section: Discussionmentioning
confidence: 99%